The Untold Story of the First Hand Transplant: Dedicated to the Memory of one of the Great Minds of the Ecuadorian Medical Community and the World - Gilbert Fernandez, Juan Jose; Febres-Cordero, Roberto Gilbert; Simpson, Roger L. (Journal of Reconstructive Microsurgery, 2019)
Background In 1964, faced with the challenge of traumatic amputation, a team of surgeons at Clinica Guayaquil was convinced that the transplantation of a hand could significantly improve function and quality of life for the recipient. With a current but basic understanding of immunosuppression, the surgeons identified a recipient and waited for the correct donor. A human hand transplant had never been performed to date.Methods The surgeons' criteria for the recipient included a young healthy individual who had sustained a traumatic amputation at the distal forearm level with full motion of the proximal joints. Communication with receiving hospitals and military facilities identified what they perceived to be a feasible donor for an allograft transplantation. Consent was obtained from the family in conjunction with the local military medical authorities and the clergy. Iced saline solution and Heparin irrigation were to be used to prepare the donor extremity. The immunosuppression regimen, limited at the time, consisted only of intravenous cortisone, Imuran, and a single dose of radiation.Results A member of the Ecuadorian marine sustained a limited blast injury that amputated his dominant hand but spared the forearm. He was transferred to the emergency department of Clinica Guayaquil. A donor who had recently died in a nearby hospital was identified not long after. A successful technical surgical transplantation was achieved. Consultants from major hospitals around the world (including Peter Bent Brigham Hospital) convened at the patient's bedside to observe the results. Despite all efforts, the patient suffered an irreversible rejection at 21 days post-transplant.Conclusion This was the first allograft transplantation of a hand. The surgeons embarked on an intervention never tried before, firmly believing that better function and quality of life would result. The bravery of this surgical team was commendable. This early surgical endeavor opened the way for future successes in transplant surgery today.
Keywords: first hand transplant; hand; transplant